Storms and the Depletion of Ammonia in Jupiter: I. Microphysics of "Mushballs". Issue 8 (5th August 2020) - Guillot, Tristan; Stevenson, David J.; Atreya, Sushil K.; Bolton, Scott J.; Becker, Heidi N.
Abstract: Microwave observations by the Juno spacecraft have shown that, contrary to expectations, the concentration of ammonia is still variable down to pressures of tens of bars in Jupiter. We show that during strong storms able to loft water ice into a region located at pressures between 1.1 and 1.5 bar and temperatures between 173 and 188 K, ammonia vapor can dissolve into water ice to form a low‐temperature liquid phase containing about one‐third ammonia and two‐third water. We estimate that, following the process creating hailstorms on Earth, this liquid phase enhances the growth of hail‐like particles that we call mushballs. We develop a simple model to estimate the growth of these mushballs, their fall into Jupiter's deep atmosphere, and their evaporation. We show that they evaporate deeper than the expected water cloud base level, between 5 and 27 bar depending on the assumed abundance of water ice lofted by thunderstorms and on the assumed ventilation coefficient governing heat transport between the atmosphere and the mushball. Because the ammonia is located mostly in the core of the mushballs, it tends to be delivered deeper than water, increasing the efficiency of the process. Further sinking of the condensates is expected due to cold temperature and ammonia‐ and water‐rich downdrafts formed by the evaporation of mushballs. This process can thus potentially account for the measurements of ammonia depletion in Jupiter's deep atmosphere. Plain Language Summary: The Juno mission has revealed that Jupiter's atmosphere is much more complex and intriguing than previously anticipated. Most of Jupiter's atmosphere was shown to be depleted in ammonia. While ammonia was expected to be well mixed, large scale variability of ammonia was detected at least 100 km below the cloud level where condensation occurs. We propose a mechanism to explain this depletion and variability. We show that in Jupiter, at very low temperatures (of order −90° C), water ice and ammonia vapor combine to form a liquid and we hypothesize that this subsequently triggers unexpected meteorology. During Jupiter's violent storms, hailstones form from this liquid, similar to the process in terrestrial storms where hail forms in the presence of supercooled liquid water. Growth of the hailstones creates a slush‐like substance surrounded by a layer of ice, and these "mushballs" fall, evaporate, and continue sinking further in the planet's deep atmosphere, creating both ammonia depletion and variability, potentially explaining the Juno observations. Key Points: We show that ammonia can melt water‐ice crystals in Jupiter's storms and lead to the formation of water‐ammonia hailstones (mushballs) These mushballs and subsequent downdrafts transport ammonia to very deep levels This can potentially explain Juno measurements that Jupiter's ammonia abundance is variable until at least 150 km below the visible clouds